Climate-smart cropping arrangement and integrated soil fertility technologies for maize and cowpea to enhance soil health, yield, and income in Malawi - Omondi, J.O.; Simwaka, P.; Kamwana, F.; Siyeni, D.; Alene, A.; Gbegbelegbe, S.; Kadwala, P.; Wupe, M.; Kyei-Boahen, S.; Chinwada, P.; Akinwale, G. (International Institute of Tropical Agriculture, 2025)
Shrinking agricultural land size, declining soil health, poor site-specific crop varieties, and minimum cropping systems diversification to combat vagaries of climate are key factors that influence yields and production in Malawi. This study aimed to develop innovations that could improve farmers’ crop yields, while enhancing their soil health, income, climate resilience, and adaptation. A study on various nutrient combinations and crop arrangements (alternating a row of maize with a row of cowpeas) was conducted in various agro-ecologies in Malawi. The nutrient combinations ranged from 0 kg N ha-1, 100 kg N ha-1, and 200 kg N ha-1 applied to maize, while cowpea received either 30 kg N ha-1, plus or no inoculant. The application of these nutrients was split into two for 100 kg N ha-1 (two halves, at planting and at six weeks after planting) and thrice for 200 kg N ha-1—25% at planting, 37.5% at three weeks after planting, and 37.5 % at six weeks after planting. These led to a total of eleven treatments being tested across three agro-ecologies of Malawi for two seasons (2020/2021 and 2021/2022) at Chitala, Mbawa and Makoka Research Stations in Salima, Mzimba and Zomba districts, respectively. Thereafter, five promising treatments with one control were subjected to on-farm trials in seven districts (Mulanje, Chiradzulu, Zomba, Salima, Mangochi, Nkhotakota, and Kasungu) across Malawi for two seasons (2022/2023 and 2023/2024). These were evaluated by farmers in terms of yields, and acceptability through participatory evaluations and economic evaluations. Altogether, the on-station, on-farm evaluations, farmer participatory evaluation, and economic analysis revealed that application of either 100 or 200 kg N ha-1 to maize with either inoculant or 30 kg N ha-1 to cowpea in an intercropping arrangement of alternating single rows of maize with cowpea were superior to current practices in terms of grain yield, land equivalent ratio, farmer perception, and net benefit returns. Therefore, we recommended the release of these technologies to combat declining soil health, climate change and improve smallholder farmers’ income, but only two were released by the Agricultural Technology Clearing Committee of Malawi. Those two were: application of 100 kg N ha-1 to maize with either: 1) inoculant or 2) 30 kg N ha-1 to cowpea in an intercropping arrangement of alternating single rows of maize with cowpea.